Development of angel-based gate in practice model for woodball - Gede Doddy Tisna MS; I Ketut Budaya Astra; I Gede Suwiwa; I Ketut Yoda (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
The purpose of this research was to develop in corner-based gate-in exercise model for woodball. This development research aims to develop in corner-based gate-in exercise model in woodball. The development uses the Luther model which includes six stages, namely: concept stage, design, material collection, manufacture, testing, and distribution. The validation step of the angle-based gate-in exercise model in woodball sports adopts the Dick, Carey, and Carey formative evaluation model which includes four stages: expert or expert evaluation, individual trials, small group trials, and field trials. The trial subjects for the development of the angle-based gate-in exercise model were the experts, athletes at FOK Undiksha Singaraja, and the Singaraja Woodball Association. The field trial phase with pretest and posttest was to determine the effectiveness of the developed model. The t-test is used to determine the effectiveness of the model. The t-test resulted in a comparison of the average pretest and post-test scores. The results of this research, namely first, is development research that aims to develop a corner-based gate-in exercise model in woodball sports using the Luther model covering six stages, namely: concept stage, design, material collection, manufacture, testing, and implementation. distribution. The content expert stated that the gate-in training model based on the shooting angle on woodball on the criteria was very good with a percentage gain of 96%. The responses to individual trials, small group trials, and large group trials were very good with percentage gains of 96%, 94.1%, and 93.6%, respectively. This means that the clarity of the material, attractiveness, and ease of use are appropriate for athletes to use.